GaN grown on nano-patterned sapphire substrates*Project supported by the Suzhou Nanojoin Photonics Co., Ltd and the High-Tech Achievements Transformation of Jiangsu Province, China (No.BA2012010). (April 2015) - Kong, Jing; Feng, Meixin; Cai, Jin; Wang, Hui; Wang, Huaibing; Yang, Hui
Abstract High-quality gallium nitride (GaN) film was grown on nano-patterned sapphire substrates (NPSS) and investigated using XRD and SEM. It was found that the optimum thickness of the GaN buffer layer on the NPSS is 15 nm, which is thinner than that on micro-patterned sapphire substrates (MPSS). An interesting phenomenon was observed for GaN film grown on NPSS:GaN mainly grows on the trench regions and little grows on the sidewalls of the patterns at the initial growth stage, which is dramatically different from GaN grown on MPSS. In addition, the electrical and optical properties of LEDs grown on NPSS were characterized.